Understanding Airborne Pathogens: Pathways, Risks, and Control Strategies - Dr V. Basil Hans (International Journal of Pathogens, 2025)
Airborne transmission is the transfer of germs through the air, mostly by respiratory droplets and aerosols that come out when you cough, sneeze, talk, or breathe. These particles can stay in the air for a long time and move a long way, especially in small or poorly ventilated places. Mycobacterium tuberculosis, measles virus, varicella-zoster virus (chickenpox), influenza virus, and more recently, SARS-CoV-2 are all infections that can be spread through the air. Infectious particles are usually between 0.5 to 5.0 micrometres in size, which lets them get deep into the respiratory system when you breathe them in. To come up with good ways to stop the spread of infections, especially in healthcare settings and crowded regions, we need to know how and why they spread via the air. To lower the risk of airborne diseases, it's important to take steps like making sure there is enough fresh air, wearing personal protection equipment (such N95 respirators), and keeping the indoor air quality at its best.
Keywords: Airborne transmission; aerosols; and infection control; and infection control. Airborne transmission; infectious agents; respiratory droplets; ventilation